Palaeographic Analysis of Codices from the Early Christian Period: A Point of Method. (September 2019) - Nongbri, Brent
It is often said that palaeographic analysis of Greek literary manuscripts from the Roman era has progressed from an aesthetic judgment to more of a science, thanks largely to increased data (in the form of newly discovered papyri and parchments from Egypt) and to more sophisticated ways of describing similarity and difference in handwriting. This progress is frequently taken to mean that we may now use the analysis of handwriting to assign dates to undated manuscripts with much greater precision and accuracy than was possible a century ago. This article questions this conclusion by focusing on neglected methodological points that speciﬁcally relate to the problem of palaeographic dating of codices, namely the size and character of the corpus of securely datable samples to which the handwriting of undated codices is compared. This problem is especially relevant for early Christian books, the surviving examples of which tend to be copied in the codex format.